Needs Assessment of Postpartum Mothers and Midwives in Early Detection of Neonatal Jaundice through a Breastfeeding Coping Approach - Listyaning Eko Martanti; Rizky Amelia; Rafika Fajrin (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2026)
Neonatal jaundice is a common condition in newborns that requires early detection and adequate breastfeeding management. Postpartum mothers often experience physical and psychological changes that may influence breastfeeding practices and their ability to recognize early signs of neonatal jaundice. Objective: This study aimed to explore the needs of postpartum mothers and midwives in newborn care related to early detection of neonatal jaundice through a breastfeeding coping approach. This qualitative study employed in-depth interviews with four postpartum and focus group discussions (FGDs) with twelve midwives. Data were analyzed thematically to identify key needs related to knowledge, attitudes, family support, experience, mentoring, and information needs. Postpartum mothers experienced various emotional responses after childbirth, including happiness, relief, fear, and anxiety, particularly among primiparous mothers. Although mothers had basic knowledge of newborn care, they lacked confidence in practical skills and early recognition of neonatal jaundice. Midwives demonstrated good knowledge of neonatal jaundice, including causes, clinical signs, initial management, and referral criteria. Family support played an important role in improving maternal confidence, breastfeeding success, and early detection of neonatal jaundice. Strengthening maternal education, family involvement, and continuous support from midwives is essential to improve early detection of neonatal jaundice through optimal breastfeeding practices.